PROBLEM DALAM ASUMSI PSIKOLOGI BEHAVIORIS (Sebuah Telaah Filsafat Ilmu) - Muthmainnah, Lailiy (Jurnal Filsafat "WISDOM", 2017)
Behaviorism as a mainstream in psychology occupies a very significant position in decades. Behaviorism developed a method that is able to overcome the shortcomings of introspection in psychology studies. There are three basic assumptions in behaviorist psychology : (1) The method of behaviorist is out-inside (from outside to inside) so that the focus of the study on psychology is behavior and not on the internal mental state. The method of behaviorist psychology is the opposition of the Cartesian model of thinking that is inside-out. (2) The purpose of psychology was the prediction of behavior. (3) The human body is mechanically qualitatively not much different with animals, just to be more complex, so that there is no qualitative difference between the behavior of humans and non-humans. Based on the above assumptions, the fundamental problem that then arises are follows: (1) Ignored or even rejection of consciousness as a part that should be considered in human behavior. (2) Explanation of a very mechanical style behaviorist only able to explain human behavior in terms of a materialist causa, formalist, and efficient, regardless of cause of finalists who put more emphasis on the intentions of the action. (3) Behaviorism too dogmatic in its aim to predict behavior. Regardless of the problems that exist in the assumptions behaviorist psychology, the flow is still able to contribute in explaining people's behavior, given the influence of the environment (both physical and social environment, cultural and economic) as a source of effective stimulus for the behavior of individuals.Â Keywords: psychological behaviorism, behavior, mechanical, behavioral prediction.